Tax Avoidance: Influencing Leverage, Capital Intensity, and Audit Quality? - Rahmawati, Eka Fitri Yunita; Darmayanti, Novi; Dientry, Abdul Manaf; Suhardiyah, Martha (The Journal of Management, Digital Business, and Entrepreneurship, 2023)
Tax is a mandatory contribution to the state used for the people's prosperity. On the other hand, tax for companies is a burden that can reduce the company's net profit. This difference in interests between the government and company management results in tax avoidance. Tax avoidance is an action taken by a company to minimize tax payments. This study aims to determine the effect of leverage, capital intensity, and audit quality on tax evasion. Tax avoidance is measured using ETR Calculation. The population in this study are property and real estate companies listed on the Indonesia Stock Exchange for the 2018-2022 period. The sample selection technique used purposive sampling and obtained a sample of 9 companies. The data analysis method in this study used linear regression with a significance of 5%. The results showed that partial leverage had a significant positive effect on tax avoidance, capital intensity did not affect tax avoidance, and audit quality significantly impacted tax avoidance. Meanwhile, simultaneously, leverage, capital intensity, and audit quality have a significant positive effect on tax avoidance.